Efficient Reactive Navigation with Exact Collision Determination for 3D Robot Shapes. (22nd May 2015) - Jaimez, Mariano; Blanco, Jose-Luis; Gonzalez-Jimenez, Javier
This paper presents a reactive navigator for wheeled mobile robots moving on a flat surface which takes into account both the actual 3D shape of the robot and the 3D surrounding obstacles. The robot volume is modelled by a number of prisms consecutive in height, and the detected obstacles, which can be provided by different kinds of range sensor, are segmented into these heights. Then, the reactive navigation problem is tackled by a number of concurrent 2D navigators, one for each prism, which are consistently and efficiently combined to yield an overall solution. Our proposal for each 2D navigator is based on the concept of the "Parameterized Trajectory Generator" which models the robot shape as a polygon and embeds its kinematic constraints into different motion models. Extensive testing has been conducted in office-like and real house environments, covering a total distance of 18.5 km, to demonstrate the reliability and effectiveness of the proposed method. Moreover, additional experiments are performed to highlight the advantages of a 3D-aware reactive navigator. The implemented code is available under an open-source licence.